PTU-074 Endoscopy enigma – cracking clinical coding in ERCP & EUS. (June 2019) - Tai, Cheh Kuan; Bryce, Kathleen; Murray, Sam
Abstract : Introduction: The coding department uses clinical information in endoscopy reports to assign a healthcare resource group tariff. The accuracy of information is important to ensure correct remuneration as well as reflecting the complexity of the procedures delivered and comorbidity of the population. We aimed to assess whether our endoscopy unit's activity is coded accurately. Methods: A list of ERCP and EUS procedures for September 2017 was generated using the 'Auditor's Tool' on Unisoft. A senior clinician and a dedicated coder examined the Unisoft reports, discharge summaries and the codes that had been assigned to each case. The findings were presented and discussed at the department meeting. The first intervention was to generate a list of 'favourite' procedures for endoscopists to include in endoscopy reports and discharge summaries. These corresponded to a set of accurate codes for the coders to use. In the second PDSA cycle, the Endoscopy QI fellow met with the dedicated coder to review the previous month's ERCP cases and adjust the codes as applicable. The aim was to assess whether regular review could further reduce inaccurate coding. In the third PDSA cycle, EUS coding was also reviewed. During this time, the 'Auditor's Tool' on Unisoft was unavailable and instead, a list of procedures coded on Cerner was generated. Results: The baseline measurement showed that 86.6% of ERCPs and 73.3% of EUS' were inaccurately coded. In the second and third cycles, the percentage of coding changes for ERCPs continued to improve leading to an average of £752 increase in remuneration per month. For EUS, the changes tended to be less marked. Following the first intervention, the corrections were mainly adding plastic or metal stent codes, adding assessment of the pancreatic duct where relevant and ensuring accurate primary diagnosis codes. Conclusion: Our QIP showed continual improvement in accuracy of coding of ERCP and EUS with time. While there is benefit in having a clinician review coding monthly, the one-off educational session for both clinicians and coders and development of formal guidance had the largest impact on coding accuracy. The improved income generated from this work has helped fund the Endoscopy QI Fellowship, ensuring the sustainability of this intervention.